Egnatia Highway and Pan-European Corridor 8: Complementarity Or Competition? - Theodoros Andrianos; Michalis Karakotsoglou; Charalampos Rizos (European Regional Science Association (ERSA), 2006)
The modern economical status and needs of regional development in Greece and the broader geographical area demand a high capacity highway, capable of fulfilling high speed requirements. Such a transportation corridor should connect Greek cities and regions with each other, as well as with neighboring countries. In Greece, Egnatia Highway is believed to be the answer to these needs. Thus, the planning and construction of Egnatia has been a major issue in Greece for several years. Egnatia highway is considered to improve connectivity between cities and regions in Greece and neighboring countries and serve their socioeconomic development. Meanwhile, in the framework of Pan-European Networks the development of Corridor 8 has been promoted. Corridor 8 crosses three countries northern of Greece and is considered by some to be competitive to Egnatia. The scope of the present paper is to investigate the relationship between Egnatia and Corridor 8. The technical and economical characteristics of these two transportation corridors are presented together with their consequences in the development of the Balkan Region. The advantages and disadvantages of these two corridors are described and how they affect each other. The cities and regions connected by these two corridors are portrayed and their prospective effects on the area are presented. Furthermore, an investigation is made on whether or not Egnatia succeeds in achieving the predefined objectives. Finally, an analysis is made about the complementarity of the two corridors in several fields.
Keywords: 330